ANALISIS DAMPAK TAMBANG EMAS DALAM KEBERLANGSUNGAN EKONOMI DAN PENINGKATAN KESEJAHTERAAN MASYARAKAT MENURUT PRESFEKTIF EKONOMI ISLAM - Fadilah, Nur Ainun (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
Huta Julu Village in Hutabargot District is one of the villages that has natural wealth in the gold mining area. Environmentally friendly gold mining has an environmental impact on society, the economy and changes in the natural environment. Everyone wants to live prosperously, have their daily needs met, and live happily. However, in this era there are still many families who are unable to live in prosperity and meet their daily living needs because of the low income of their family members or partners. That's why the Hutajulu residents decided to work on this gold mine. The aim of this research is to determine the impact of gold mining on economic sustainability and improving community welfare. This research is a qualitative descriptive research with an exploratory approach. Information was collected through direct observation and interviews in the field. The findings show that gold mining management has positive and negative impacts on society and the environment.